2020
DOI: 10.1097/sla.0000000000003435
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Negative Pressure Wound Therapy for Closed Laparotomy Incisions

Abstract: Objective: The aim of this study was to determine whether negative pressure wound therapy (NPWT) applied to primarily closed incisions decreases surgical site infections (SSIs) following open abdominal surgery. Background: SSIs are a common cause of morbidity following open abdominal surgery. Prophylactic NPWT has shown promise for SSI reduction. However, the results of randomized controlled trials (RCTs) conducted among patients undergoing laparotomy h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 30 publications
1
44
0
1
Order By: Relevance
“…However, to date there has been a lack of consensus on the routine use of NPWT following for all laparotomies, not just focusing on emergency cases. A meta-analysis in 2018 noted a decrease in overall SSI rates in NPWT patients [34], but there was considerable heterogeneity in the type of studies included, with one major critique being the inclusion of a RCT which applied NPWT to open rather than closed incisions [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…However, to date there has been a lack of consensus on the routine use of NPWT following for all laparotomies, not just focusing on emergency cases. A meta-analysis in 2018 noted a decrease in overall SSI rates in NPWT patients [34], but there was considerable heterogeneity in the type of studies included, with one major critique being the inclusion of a RCT which applied NPWT to open rather than closed incisions [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, Kuper et al [ 62 ] conducted another meta-analysis and found no difference in the outcome between iNPWT and SD — with high heterogeneity between patient groups.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent experimental study in pigs, incisional wounds with extensive dead space were created on the dorsum to study the effect of ciNPWT applied for seven days concurrently with aspiration drains, and the authors described a significant decrease in the seroma drainage (through the drains) in the treatment group compared to the control group (Suh et al, 2016). From another perspective, in the current human literature, an extensive variety in the duration to apply ciNPWT treatment has been reported, ranging from a few days till more than ten days with most performed four-day protocols (Li et al, 2017;O'Leary et al, 2017;Shen et al, 2017;Kuper et al, 2020). Furthermore, longer treatments also involve longer hospitalization time and higher costs, which may be a limitation to the extended use of ciNPWT in veterinary patients (Gaus et al, 2017).…”
Section: Dorsal Middle Ventralmentioning
confidence: 99%
“…Some authors claim prevention of surgical site infections by using ciNPWT (Fernandez et al, 2019;Tran et al, 2019). However, data are not consistent regarding this advantage (Masden et al, 2012;Shen et al, 2017;Kuper et al, 2020). Unfortunately, the studies mentioned above did never focus on reporting pain scores.…”
Section: Introductionmentioning
confidence: 99%